Five Year Plan Progress Report for 1954-55 - Planning Commission (Planning Commission, 1956)
FOR the first half of 1954-55 the Planning Commission issued a progress report in April 1955. The present report provides information for 1954-55 as a whole. During the past year the staff of the Planning Commission, Central Ministries as well as State Governments has been preoccupied with the preparation of the Second Five Year Plan. There has therefore been some delay in the publication of this report. Although the report relates specifically to 1954-55, it has been possible to include in it some information relating to the past year.
Government of India, Planning Commission